2000
DOI: 10.1016/s0002-9440(10)64529-4
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Bleomycin-Induced Pulmonary Fibrosis in Mice Deficient for Components of the Fibrinolytic System

Abstract: Acute and chronic pulmonary diseases are characterized by impaired fibrinolytic activity within the lung. To determine the role of the fibrinolytic system in regulating the pathologies associated with lung injury, we examined the effect of bleomycin, an agent that induces the development of pulmonary fibrosis, in mice deficient for plasminogen (Pg(-)(/-)), urokinase (u-PA(-)(/-)), urokinase receptor (u-PAR(-)(/-)), or tissue plasminogen activator (t-PA(-)(/-)), and in control wild-type (WT) mice. Pg(-)(/-) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 38 publications
7
105
2
1
Order By: Relevance
“…As stated previously, Swaisgood and colleagues 23 found similar effects in the lungs of uPAdeficient mice after bleomycin treatment. Histologically, the lungs appeared fibrotic with major structural changes in the alveoli and abundant inflammatory cell infiltrate, but HPLC analysis of the hydroxyproline content in these tissues showed that collagen levels remained unchanged compared with their wild-type counterparts.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…As stated previously, Swaisgood and colleagues 23 found similar effects in the lungs of uPAdeficient mice after bleomycin treatment. Histologically, the lungs appeared fibrotic with major structural changes in the alveoli and abundant inflammatory cell infiltrate, but HPLC analysis of the hydroxyproline content in these tissues showed that collagen levels remained unchanged compared with their wild-type counterparts.…”
Section: Discussionsupporting
confidence: 70%
“…An association between reduced fibrinolysis and the development of fibrosis has been highlighted in other pathological experimental model systems in studies similar to ours using mice with overexpression or underexpression of various components of the fibrinolytic system. 22,23,34,35 Eitzman and colleagues 22 found that overexpression of PAI-1, resulted in enhanced deposition of collagen in the lungs of bleomycin-treated mice, whereas PAI-1-deficient mice produced levels of collagen comparable to wildtype controls. Of particular interest, a study by Swaisgood and colleagues 23 also using PA-deficient mice, showed that bleomycin-instillation resulted in approximately a twofold increase in the amount of collagen in the lungs of tPA-deficient mice compared with uPA-deficient and wild-type mice directly correlating with findings in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibrinolytic activity that is normally present in bronchoalveolar lavage (BAL) fluid is depressed in patients with many types of lung injury due to increased levels of plasminogen activator inhibitors, particularly plasminogen activator inhibitor (PAI)-1 (3-7). The importance of this perturbation has been demonstrated in animal models where suppression of plasminogen activator activity worsens fibrosis, whereas enhanced plasminogen activator activity limits scarring (8)(9)(10)(11)). An obvious explanation for the link between suppressed fibrinolysis and fibrosis is that successful repair requires the timely removal of the fibrin-rich provision matrix that accumulates after tissue injury.…”
mentioning
confidence: 99%
“…Bleomycin sulphate (0.015 U/ 30 μL/mouse, Sigma, Poole, UK) was administered as previously described [19].…”
Section: Bleomycin-induced Model Of Ipfmentioning
confidence: 99%